1989
DOI: 10.1099/00221287-135-12-3219
|View full text |Cite
|
Sign up to set email alerts
|

Surface-exposed Epitopes on the Major Outer-membrane Protein of Chlamydia trachomatis Defined with Peptide Antisera

Abstract: The surface exposure of computer-predicted, linear B-cell epitopes on the major outer-membrane protein (MOMP) of Chlamydia trachomatis serovar B was assessed using antibodies raised against synthetic peptides in conjunction with immunogold transmission electron microscopy. Several of the chosen peptides elicited antibodies which reacted with both denatured and native MOMP. The majority of the exposed epitopes were found within the variable segments of MOMP. For each of the epitopes identified, the extent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…We speculate that the unique peptide ANELP in the equivalent position in C. pneumoniae MOMP is also surface exposed and this may represent a type-specific region. In VS 4 of the B complex serovars of C. trachomatis there are two known subspecies-and one species-specific epitope (Baehr et al, 1988;Conlan et al, 1988Conlan et al, , 1989. We are unable to identify a clear counterpart in C. pneumoniae.…”
Section: Discussionmentioning
confidence: 52%
“…We speculate that the unique peptide ANELP in the equivalent position in C. pneumoniae MOMP is also surface exposed and this may represent a type-specific region. In VS 4 of the B complex serovars of C. trachomatis there are two known subspecies-and one species-specific epitope (Baehr et al, 1988;Conlan et al, 1988Conlan et al, , 1989. We are unable to identify a clear counterpart in C. pneumoniae.…”
Section: Discussionmentioning
confidence: 52%
“…The MOMP, which is found in both EBs and RBs, is thought to act as a porin (Bavoil etal., 1984) and has a role in the attachment and uptake of EBs by host cells. It is also recognized as an exposed surface molecule possessing infection-neutralizing epitopes (Collett e t al., 1989 ;Zhang e t al., 1989 ;Conlan et al, 1989 ;Conlan et al, 1990;Peterson e t al., 1990). Polyacrylamide gel analysis of C. tracbomatis proteins has shown that the 60 kDa CrP occurs as a singlet in the trachoma biovar and as a 60/62 kDa doublet in the LGV biovar (Batteiger e t d., 1985).…”
Section: Members Of the Genusmentioning
confidence: 99%
“…Hence, this reactivity is unlikely to account for the observed species-specific labelling of intact chlamydiae. However, VS IV appears to be immunologically complex, as two surface-exposed, subspecies-specific epitopes flank each side of the speciesspecific region (Conlan et al, 1988(Conlan et al, , 1989b.…”
Section: Discussionmentioning
confidence: 99%
“…Surface-exposed epitopes of MOMP on intact chlamydiae were detected by transmission electron microscopy (TEM) using immunogold as previously described (Conlan et al, 1989b). Test antisera were used at dilutions of 1 : 10 and 1 : 50; the protein G-gold conjugate was used at 1 : 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation